(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2020)
The study of the reproductive biology of the red mangrove (Rhizophora mangle L.) in Puerto El Morro, Guayas Province, Ecuador, aims to determine that the species is hermaphrodite, describing its reproductive organs, its state and maturation process from flower bud to anthesis, establishing the respective morphological characteristics and sizes. In addition, to classify the reproductive status with respect to the other species of red mangrove in Puerto El Morro mangroves, which currently maintains few flowered R. mangle trees and a low representativeness ratio in the mangroves of Puerto El Morro. For this purpose, two plots corresponding to 0.25 ha were made, both at the entrance and exit of the canal El Morro channel, which allowed establishing the morphology of R. mangle, its density and volume in each plot, and in relation to the other related species of red mangroves present.